2004
DOI: 10.1002/bjs.4427
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in plasma selenium concentration after cadaveric renal transplantation

Abstract: Low plasma selenium concentrations are common at the time of transplantation but appear to normalize thereafter. The identification of low selenium levels in patients who experience CAR or CMV (two important risk factors for clinically apparent CGN) suggests that the relationship between selenium and CGN warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…In addition, these drugs seem to play an important role in endothelin-induced arterial hypertension, which may additionally contribute to the oxidant stress [33]. However, there are several reports arguing against the increased oxidative stress due to calcineurin-inhibiting drugs [9,10,11, 34, 35]. The discrepancies of the above reports may come out of the diverse properties of the study groups, methods and dosages of the drugs.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…In addition, these drugs seem to play an important role in endothelin-induced arterial hypertension, which may additionally contribute to the oxidant stress [33]. However, there are several reports arguing against the increased oxidative stress due to calcineurin-inhibiting drugs [9,10,11, 34, 35]. The discrepancies of the above reports may come out of the diverse properties of the study groups, methods and dosages of the drugs.…”
Section: Discussionmentioning
confidence: 60%
“…Also, statins and ACE inhibitors, which are widely used in CRF have antioxidant effects [24, 25]. Moreover, the presence of infections or chronic graft nephropathies may worsen the oxidative stress [10, 26]. The period of cold ischemic preservation can also cause generation of reactive oxygen species (ROS) and consequent tissue injury [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next two months there was a further, slight increase in Se concentration. Morris-Stiff et al (2005) have shown that in 30, out of 40 patients before transplantation Se level in plasma was lower than in healthy subjects, but this was normalized in the majority of patients within 3 months. A decrease of Se in the first few days after surgery in our study is very likely associated with the restricted protein intake (the main source of Se) just after surgery.…”
Section: Antioxidants In Patients After Kidney Transplantation and Thmentioning
confidence: 92%